Dziewictwo Maryi w zrodzeniu Chrystusa na podstawie kazań św. Augustyna na Boże Narodzenie - Jaśkiewicz, Sylwester (Verbum Vitae, 2024)
In the context of contemporary culture and mentality, Mary’s virginity in giving birth to Christ might seem a completely archaic and even absurd issue. The only way to overcome this obstacle could involve providing believers with more convincing explanations and substantive and source-based justifications. Against this background, referring to the authority of St. Augustine and his Christmas sermons (In Natali Domini), is not accidental. The article attempts, first of all, to show the birth from the Virgin (Virginis partus) and its message coming from the Christmas teaching of the Bishop of Hippo, which is also the basis of his Mariology. Augustine sees the issue of Mary’s virginity during childbirth (in partu) as a constitutive element of her lasting virginity, which is how it should be understood today.